Relationship of Husband Support and Communication Ability of Family Planning Field Officers with New Family Planning Achievements in the District of Poleang Timur - Yunita; Binekada, I Made Christian; Zainuddin, Asnia (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2021)
In family planning services, contraceptive users have the right to obtain complete information about various contraceptive methods, their advantages and disadvantages, the right to receive comprehensive care, the right of women's autonomy to care for their health and determine their reproduction, and the right to decide whether to have children or not to have children, and to determine the number of children desired, and the period of birth of the child. The purpose of this study was to determine the relationship between husband's support and communication skills of family planning field officers (FPFO) with the achievement of new Family Planning (FP) in Poleang Timur District. This type of research is a survey using a cross sectional study design. The number of samples as many as 95 respondents with the sampling technique is proportional random sampling. Collecting data by using a questionnaire. Data analysis using Chi Square test. The results showed that there was a relationship between husband's support and new family planning achievement, p value = 0.038 <0.05 and there was a relationship between FPFO communication skills, p value = 0.007 <0.05, with new family planning achievement. Conclusion; there is a relationship between husband's support and communication skills of FPFO with the achievement of new family planning in Poleang Timur District, Regency Bombana. Suggestion; the need for husband's support and improvement of FPFO communication skills in optimizing new family planning program services.